Restriction of memory B cell differentiation at the germinal center B cell positive selection stage - Toboso-Navasa, Amparo; Gunawan, Arief; Morlino, Giulia; Nakagawa, Rinako; Taddei, Andrea; Damry, Djamil; Patel, Yash; Chakravarty, Probir; Janz, Martin; Kassiotis, George; Brink, Robert; Eilers, Martin; et al. (The Journal of experimental medicine, 2020)
Memory B cells (MBCs) are key for protection from reinfection. However, it is mechanistically unclear how germinal center (GC) B cells differentiate into MBCs. MYC is transiently induced in cells fated for GC expansion and plasma cell (PC) formation, so-called positively selected GC B cells. We found that these cells coexpressed MYC and MIZ1 (MYC-interacting zinc-finger protein 1 [ZBTB17]). MYC and MIZ1 are transcriptional activators; however, they form a transcriptional repressor complex that represses MIZ1 target genes. Mice lacking MYC–MIZ1 complexes displayed impaired cell cycle entry of positively selected GC B cells and reduced GC B cell expansion and PC formation. Notably, absence of MYC–MIZ1 complexes in positively selected GC B cells led to a gene expression profile alike that of MBCs and increased MBC differentiation. Thus, at the GC positive selection stage, MYC–MIZ1 complexes are required for effective GC expansion and PC formation and to restrict MBC differentiation. We propose that MYC and MIZ1 form a module that regulates GC B cell fate.